Solid electrolyte and preparation method thereof, battery and electric equipment

By dispersing the polymer lithium salt in the solid electrolyte and building a conductive layer on the surface, the problems of poor interface compatibility between the solid electrolyte and the electrode and large interface impedance are solved, high ionic conductivity and low interface impedance are achieved, and the performance of solid-state batteries is improved.

CN119674212APending Publication Date: 2025-03-21BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411894342.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The poor compatibility of solid-state electrolytes at the electrode interface, large interface impedance and low ionic conductivity limit the research progress of solid-state batteries.

Method used

A solid electrolyte including a base film, a polymer lithium salt and a conductive layer is used, and the polymer lithium salt is dispersed in the base film, and the conductive layer is arranged on a partial surface of the base film to improve compatibility with the electrode interface and electronic conductivity.

Benefits of technology

It realizes high compatibility, low interface impedance and high ionic conductivity between the solid-state electrolyte and the electrode interface, and improves the performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201335460000131
    Figure BDA0005201335460000131
  • Figure BDA0005201335460000141
    Figure BDA0005201335460000141
  • Figure HDA0005201335470000011
    Figure HDA0005201335470000011
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a solid electrolyte and a preparation method thereof, a battery and electric equipment, the solid electrolyte comprises a base membrane, a polymer lithium salt and a conductive layer, the polymer lithium salt is dispersed in the base membrane; the conductive layer is disposed on at least a portion of the surface of the base film. Therefore, the solid electrolyte has relatively high ionic conductivity, relatively low interface impedance and relatively high flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a solid electrolyte and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In recent years, with the rapid development of industries such as telecommunications and electric vehicles, rechargeable batteries for power and energy storage purposes have also shown rapid growth. The improvement of global environmental protection requirements and the development of new transportation tools such as electric vehicles will promote the rapid development of battery industries such as lithium-ion batteries, lithium-sulfur batteries and lithium-air batteries. However, there are certain safety issues in the actual application of rechargeable batteries, mainly because the organic electrolyte is prone to volatilization and leakage, which can easily induce safety accidents such as fire and explosion. All-solid-state batteries made of solid electrolytes use solid electrolytes as ion conductors to achieve the transfer of lithium ions between positive and negative active materials, and can also be used as diaphragms to separate positive and negative electrodes to prevent internal short circuits, greatly improving the safety performance of batteries. However, solid electrolytes have the disadvantages of poor compatibility with the electrode interface, large interface impedance, and low ionic conductivity, which limit the research progress of solid-state batteries. Therefore, research and development of solid electrolytes with high compatibility with the electrode interface and high performance has become the key to the development of rechargeable batteries. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a solid electrolyte with high ionic conductivity, low interface impedance or high flexibility, a preparation method thereof, a battery and an electrical device.

[0004] In a first aspect, the present application proposes a solid electrolyte, comprising: a base film, a polymer lithium salt and a conductive layer, wherein the polymer lithium salt is dispersed in the base film; and the conductive layer is disposed on at least a portion of the surface of the base film. Thus, the solid electrolyte has good compatibility with the electrode interface, and has high ionic conductivity and low interface impedance.

[0005] In some embodiments, the polymer lithium salt includes at least one of lithium carboxymethyl cellulose and lithiated polyacrylic acid, so that the material source is wide, which is beneficial to improve the ionic conductivity of the solid electrolyte.

[0006] In some embodiments, the number average molecular weight of the lithium carboxymethyl cellulose is 10 5 ~10 6 The number average molecular weight of the lithiated polyacrylic acid is 500 to 5000. This can further improve the ionic conductivity of the solid electrolyte.

[0007] In some embodiments, the thickness of the conductive layer is 50 nm to 2 μm, which is helpful to improve the problem of large contact resistance between the solid electrolyte and the electrode.

[0008] In some embodiments, the conductive layer includes at least one of a granular conductive material and a linear conductive material; in other embodiments, the conductive layer includes a granular conductive material and a linear conductive material. This can improve the electronic conductivity of the interface between the solid electrolyte and the electrode and reduce the interface contact resistance.

[0009] In some embodiments, the particulate conductive material includes conductive carbon black.

[0010] In some embodiments, the conductive carbon black includes at least one of Super P, acetylene black, and Ketjen black. Thus, the material source is wide and the cost is low.

[0011] In some embodiments, the particle size of the conductive carbon black is 20 nm to 50 nm, and the specific surface area is 50 m 2 / g~1500m 2 / g, and the oil absorption value is 300mL / 100g~800mL / 100g. This is more conducive to providing a short-range conductive network for the solid electrolyte.

[0012] In some embodiments, the linear conductive material includes at least one of carbon nanotubes and carbon nanofibers.

[0013] In some embodiments, the carbon nanotubes have a diameter of 2 nm to 30 nm, a length of 5 μm to 50 μm, and a specific surface area of ​​300 m 2 / g~1000m 2 In some embodiments, the carbon nanofibers have a diameter of 100 μm to 200 μm, a length of 5 μm to 10 μm, and a specific surface area of ​​200 m 2 / g~500m 2 / g. This is more conducive to providing a long-range conductive network for the solid electrolyte.

[0014] In some embodiments, the base film includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, and a polymer solid electrolyte. Thus, the material source is wide and the cost is low.

[0015] In some embodiments, the base film has a thickness of 80 μm to 100 μm.

[0016] In some embodiments, the ionic conductivity of the solid electrolyte is 10 -3 S / cm~10 -1 S / cm 。 Therefore, the solid electrolyte has high ionic conductivity.

[0017] The second aspect of the present application provides a method for preparing a solid electrolyte, comprising:

[0018] The polymer lithium salt and the base film are mixed and stirred in a solvent, and vacuumed and heated to obtain a solid electrolyte membrane;

[0019] The conductive material is sprayed onto the solid electrolyte membrane to obtain the solid electrolyte.

[0020] The present application uses high-pressure jetting technology to deposit conductive materials on the surface of a solid electrolyte membrane, constructs a conductive network on the surface of the solid electrolyte membrane, greatly improves the electronic conductivity of the interface between the solid electrolyte and the electrode, and effectively reduces the interface contact resistance.

[0021] In some embodiments, the mass ratio of the polymer lithium salt to the base film is 0.5-2.5:99.5-97.5; in other embodiments, the mass ratio is 1-2:99-98; in some specific examples, the mass ratio is 1.5:98.5. This is conducive to improving preparation efficiency and reducing costs.

[0022] In some embodiments, the stirring speed is 1000 r / min to 3000 r / min; in other embodiments, the stirring speed is 1500 r / min to 2500 r / min; in some specific examples, the stirring speed is 2000 r / min. This is conducive to promoting the reaction and increasing the reaction rate.

[0023] In some embodiments, the heating temperature is 100° C. to 150° C., in other embodiments, the heating temperature is 110° C. to 130° C., and in some specific examples, the heating temperature is 125° C. This is conducive to promoting the reaction and increasing the reaction rate.

[0024] The third aspect of the present application provides a battery, comprising the solid electrolyte described in the first aspect of the present application or the solid electrolyte prepared by the method described in the second aspect of the present application. Thus, the battery has excellent conductivity and rate performance.

[0025] The fourth aspect of the present application provides an electrical device, comprising the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the solid electrolyte of an embodiment of the present application.

[0027] Reference numerals:

[0028] 10-base film; 20-polymer lithium salt; 30-conductive carbon black; 40-carbon nanotubes. DETAILED DESCRIPTION

[0029] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0030] The first aspect of the present application proposes a solid electrolyte, referring to Figure 1 , the solid electrolyte comprises: a base film 10, a polymer lithium salt 20, a conductive carbon black 30, and a carbon nanotube 40; wherein the polymer lithium salt is dispersed in the base film; the conductive carbon black and the carbon nanotube are arranged on at least part of the surface of the base film. The present application disperses the polymer lithium salt in the base film, which can dissociate lithium ions during the charge and discharge process, thereby improving the ionic conductivity of the solid electrolyte, which is conducive to solving the current problem of low ionic conductivity of solid electrolytes. In addition, the surface of the solid electrolyte is coated with a conductive layer, which can improve the electronic conductivity of the solid electrolyte membrane in contact with the electrode interface, solving the current problem of large contact resistance between the solid electrolyte and the electrode. Finally, since the base film is filled with a polymer lithium salt, which is a long-chain structure and has a certain degree of flexibility, it can solve the current problem of hard solid electrolyte membranes.

[0031] In some embodiments, the polymer lithium salt includes at least one of lithium carboxymethyl cellulose and lithiated polyacrylic acid, wherein the lithium carboxymethyl cellulose and lithiated polyacrylic acid can be mixed in any proportion. The polymer lithium salt is a long chain structure with a certain degree of flexibility. Dispersing it in the solid electrolyte base film is conducive to solving the problem that the current solid electrolyte membrane is relatively hard.

[0032] In some embodiments, the number average molecular weight of the lithium carboxymethyl cellulose is 10 5 ~10 6 , for example, it can be 100000, 200000, 300000, 400000, 500000, 600000, 700000, 800000, 900000 or 1000000, etc.; the number average molecular weight of the lithiated polyacrylic acid is 500 to 5000, for example, it can be 500, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500 or 5000, etc. Thus, the ionic conductivity of the solid electrolyte can be further improved.

[0033] In some embodiments, the thickness of the conductive layer is 50 nm to 2 μm, for example, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 1.5 μm or 2 μm, etc. Within the above thickness range, it is beneficial to reduce the interface contact impedance between the solid electrolyte and the electrode.

[0034] In some embodiments, the conductive layer includes at least one of a granular conductive material and a linear conductive material; in other embodiments, the conductive layer includes a granular conductive material and a linear conductive material. It can be understood that the granular conductive material provides a short-range conductive network, and the linear conductive material provides a long-range conductive network. The conductive layer can include only granular conductive materials or linear conductive materials, or both granular conductive materials and linear conductive materials, which can be flexibly selected according to specific needs.

[0035] In some embodiments, the granular conductive material includes conductive carbon black, and the conductive carbon black includes at least one of Super P, acetylene black, and Ketjen black. Thus, the material source is wide and the cost is low.

[0036] In some embodiments, the particle size of the conductive carbon black is 20 nm to 50 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, and the specific surface area is 50 m 2 / g~1500m 2 / g, for example, 50m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g, 600m 2 / g、700m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g or 1500m 2 / g, etc., and the oil absorption value is 300mL / 100g to 800mL / 100g, for example, it can be 300mL / 100g, 400mL / 100g, 500mL / 100g, 600mL / 100g, 700mL / 100g or 800mL / 100g.

[0037] In some embodiments, the carbon nanotubes have a diameter of 2 nm to 30 nm, such as 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm or 30 nm, etc., a length of 5 μm to 50 μm, such as 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc., and a specific surface area of ​​300 m 2 / g~1000m 2 / g, for example, 300m 2 / g, 400m 2 / g、500m 2 / g, 600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g or 1000m 2 / g, etc.

[0038] In some embodiments, the carbon nanofibers have a diameter of 100 μm to 200 μm, such as 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm, etc., a length of 5 μm to 10 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., and a specific surface area of ​​200 m 2 / g~500m 2 / g, for example, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g, etc.

[0039] It should be noted that the particle size of conductive carbon black is tested using a particle size analyzer, the specific surface area is tested using a specific surface area analyzer, the oil absorption value is calculated using the weight of DBP oil that 100g of carbon black can absorb; the diameter and length of carbon nanotubes or carbon nanofibers are tested using an electron microscope.

[0040] In some embodiments, the base film includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, and a polymer solid electrolyte. Thus, the material source is wide and the cost is low.

[0041] In some embodiments, the base film has a thickness of 80 μm to 100 μm, for example, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm.

[0042] In some embodiments, the ionic conductivity of the solid electrolyte is 10 -3 S / cm~10 -1 S / cm, for example, can be 10 -3 S / cm, 10 -2 S / cm or 10 -1 S / cm, etc. Therefore, the solid electrolyte has a higher ionic conductivity.

[0043] The second aspect of the present application provides a method for preparing a solid electrolyte, comprising:

[0044] S1: Mixing the polymer lithium salt and the base film in a solvent, stirring, vacuumizing and heating to obtain a solid electrolyte membrane.

[0045] Specifically, the base film and the polymer lithium salt can be dissolved in N-methylpyrrolidone (NMP) solvent and stirred, and then the container is evacuated and heated until the solvent is completely removed to obtain a solid electrolyte membrane with a fixed shape.

[0046] In some embodiments, the mass ratio of the polymer lithium salt to the base film is 0.5-2.5:99.5-97.5, for example, 0.5:99.5, 1:99, 1.5:98.5, 2:98 or 2.5:97.5, etc. In other embodiments, the mass ratio is 1-2:99-98; in some specific examples, the mass ratio is 1.5:98.5. This is conducive to improving preparation efficiency and reducing costs.

[0047] In some embodiments, the stirring speed is 1000 r / min to 3000 r / min, for example, 1000 r / min, 1500 r / min, 2000 r / min, 2500 r / min or 3000 r / min, etc. In other embodiments, the stirring speed is 1500 r / min to 2500 r / min; in some specific examples, the stirring speed is 2000 r / min. This is conducive to promoting the reaction and increasing the reaction rate.

[0048] In some embodiments, the heating temperature is 100° C. to 150° C., for example, 100° C., 110° C., 120° C., 130° C., 140° C. or 150° C., etc. In other embodiments, the heating temperature is 110° C. to 130° C., and in some specific examples, the heating temperature is 125° C. This is conducive to promoting the reaction and increasing the reaction rate.

[0049] S2: Spraying a conductive material onto the solid electrolyte membrane to obtain the solid electrolyte.

[0050] Specifically, one or more of the conductive carbon black, carbon nanotubes and carbon nanofibers may be deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique, so that a conductive layer is obtained on the surface of the solid electrolyte membrane.

[0051] The present application improves the ionic conductivity and membrane flexibility of the solid electrolyte by filling a certain proportion of polymer lithium salt in the base membrane; in addition, a high-pressure spraying technology is used to deposit a conductive material on the surface of the base membrane, thereby reducing the interface contact resistance between the solid electrolyte and the electrode.

[0052] The third aspect of the present application provides a battery, comprising the solid electrolyte described in the first aspect of the present application or the solid electrolyte prepared by the method described in the second aspect of the present application. Thus, the battery has excellent conductivity and cycle performance.

[0053] It can be understood that there is no particular limitation on the specific type of the battery, which may be a primary battery, a secondary battery (including but not limited to lithium-ion batteries, lithium-sulfur batteries, lithium-air batteries and other storage batteries); the shape of the battery may be a cylindrical battery, a square battery or a battery of any other shape, etc., and according to the outer packaging classification, the battery may be a hard shell battery, a soft pack battery, etc.

[0054] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte, wherein the positive electrode sheet, the negative electrode sheet, and the solid electrolyte can be made into an electrode assembly by winding or laminating processes, and the electrode assembly is contained in an outer package. During the battery charge and discharge process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The solid electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet, and at the same time acts as a diaphragm to prevent the positive and negative electrodes from short-circuiting.

[0055] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a conductive agent and a binder, and the positive electrode current collector may include a metal foil, for example, the metal foil may be an aluminum foil. The positive electrode active material may include lithium nickel cobalt manganese oxide (NCM811), lithium nickel cobalt manganese oxide (613), lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials or positive electrode active materials commonly used in the art. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.

[0056] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.

[0057] The fourth aspect of the present application provides an electrical device, comprising the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here.

[0058] According to an embodiment of the present application, the battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0059] The embodiments of the present application are described in detail below.

[0060] Example 1

[0061] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 5 ) and an oxide solid electrolyte (thickness of 90 μm) are dissolved in an NMP solvent at a mass ratio of 1.5:98.5, stirred and mixed evenly at a speed of 2000 r / min, and then the container is vacuum-heated at a heating temperature of 125° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0062] (2) Super P (particle size 30nm, specific surface area 1000m 2 / g, oil absorption value is 500mL / 100g), carbon nanotubes (diameter is 15nm, length is 30nm, specific surface area is 500m 2 / g) and carbon nanofibers (diameter 150nm, length 8nm, specific surface area 300m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 2 μm, thereby finally obtaining a solid electrolyte.

[0063] Example 2

[0064] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 5 ) and an oxide solid electrolyte (thickness of 90 μm) are dissolved in an NMP solvent at a mass ratio of 0.5:99.5, stirred and mixed evenly at a speed of 2000 r / min, and then the container is vacuum-heated at a heating temperature of 125° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0065] (2) Super P (particle size 30nm, specific surface area 1000m 2 / g, oil absorption value is 500mL / 100g), carbon nanotubes (diameter is 15nm, length is 30nm, specific surface area is 500m 2 / g) and carbon nanofibers (diameter 150nm, length 8nm, specific surface area 300m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 2 μm, thereby finally obtaining a solid electrolyte.

[0066] Example 3

[0067] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 5 ) and an oxide solid electrolyte (thickness of 90 μm) are dissolved in an NMP solvent at a mass ratio of 2.5:97.5, stirred and mixed evenly at a speed of 2000 r / min, and then the container is vacuum-heated at a heating temperature of 125° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0068] (2) Super P (particle size 30nm, specific surface area 1000m 2 / g, oil absorption value is 500mL / 100g), carbon nanotubes (diameter is 15nm, length is 30nm, specific surface area is 500m 2 / g) and carbon nanofibers (diameter 150nm, length 8nm, specific surface area 300m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 2 μm, thereby finally obtaining a solid electrolyte.

[0069] Example 4

[0070] (1) dissolving lithiated polyacrylic acid (number average molecular weight of 3000) and sulfide solid electrolyte (thickness of 100 μm) in NMP solvent at a mass ratio of 1.5:98.5, stirring and mixing at a speed of 3000 r / min, and then vacuuming and heating the container at a heating temperature of 150° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0071] (2) Acetylene black (particle size 50 nm, specific surface area 1500 m 2 / g, oil absorption value is 800mL / 100g), carbon nanotubes (diameter is 30nm, length is 50nm, specific surface area is 1000m 2 / g) and carbon nanofibers (diameter 200nm, length 10nm, specific surface area 500m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 1 μm, and finally a solid electrolyte is obtained.

[0072] Example 5

[0073] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 6 ) and a polymer solid electrolyte (with a thickness of 80 μm) are dissolved in an NMP solvent at a mass ratio of 1.5:98.5, stirred and mixed evenly at a speed of 1000 r / min, and then the container is vacuum-heated at a heating temperature of 100° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0074] (2) Super P (particle size 30nm, specific surface area 1000m 2 / g, oil absorption value of 500mL / 100g) and carbon nanotubes (diameter of 15nm, length of 30nm, specific surface area of ​​500m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 2 μm, thereby finally obtaining a solid electrolyte.

[0075] Example 6

[0076] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 6 ) and a polymer solid electrolyte (with a thickness of 80 μm) are dissolved in an NMP solvent at a mass ratio of 1.5:98.5, stirred and mixed evenly at a speed of 1000 r / min, and then the container is vacuum-heated at a heating temperature of 100° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0077] (2) Super P (particle size 30nm, specific surface area 1000m 2 / g, oil absorption value is 500mL / 100g) is deposited on the surface of the solid electrolyte membrane using high-pressure spraying technology to form a conductive layer with a thickness of 2μm, and finally a solid electrolyte is obtained.

[0078] Example 7

[0079] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 6 ) and a polymer solid electrolyte (with a thickness of 80 μm) are dissolved in an NMP solvent at a mass ratio of 1.5:98.5, stirred and mixed evenly at a speed of 1000 r / min, and then the container is vacuum-heated at a heating temperature of 100° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0080] (2) Carbon nanofibers (diameter 200 nm, length 10 nm, specific surface area 500 m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 2 μm, thereby finally obtaining a solid electrolyte.

[0081] Example 8

[0082] (1) Lithium carboxymethyl cellulose (number average molecular weight 10 6 ) and a polymer solid electrolyte (with a thickness of 80 μm) are dissolved in an NMP solvent at a mass ratio of 1.5:98.5, stirred and mixed evenly at a speed of 1000 r / min, and then the container is vacuum-heated at a heating temperature of 100° C. until the solvent is completely removed, thereby obtaining a solid electrolyte membrane;

[0083] (2) Carbon nanotubes (diameter 15 nm, length 30 nm, specific surface area 500 m 2 / g) is deposited on the surface of the solid electrolyte membrane using a high-pressure spraying technique to form a conductive layer with a thickness of 2 μm, thereby finally obtaining a solid electrolyte.

[0084] Comparative Example 1

[0085] Lithium carboxymethyl cellulose (number average molecular weight 10 5 ) and an oxide solid electrolyte (with a thickness of 90 μm) are dissolved in an NMP solvent at a mass ratio of 1.5:98.5, stirred and mixed evenly at a speed of 2000 r / min, and then the container is vacuum-heated at a heating temperature of 125°C until the solvent is completely removed to obtain a solid electrolyte.

[0086] Comparative Example 2

[0087] Super P (particle size 30nm, specific surface area 1000m 2 / g, oil absorption value is 500mL / 100g) is deposited on the surface of the oxide solid electrolyte (thickness is 90μm) using high-pressure spraying technology to form a conductive layer with a thickness of 2μm to obtain a solid electrolyte.

[0088] Test method:

[0089] (1) Ionic conductivity: A solid electrolyte sample is placed between two electrodes. An AC voltage of a certain frequency and amplitude is applied through an AC power supply. The phase difference between the current and voltage is measured simultaneously. The ionic conductivity of the electrolyte is then calculated based on the impedance model of the AC circuit.

[0090] (2) Interface resistance: The solid electrolyte membrane and the positive electrode or negative electrode are pressed into a mold of a certain size to form a diameter of 10 cm. 2 The interface resistance between the electrode and the solid electrolyte is tested using a four-probe resistance tester.

[0091] (3) Toughness: The solid electrolyte membrane is folded 180° repeatedly n times to observe whether the electrolyte membrane breaks to determine its toughness.

[0092] The test results are shown in the following table:

[0093] Table 1 Test results

[0094]

[0095]

[0096] It can be seen from Table 1 that compared with the comparative example, the ionic conductivity and toughness of Examples 1 to 8 are improved, and the interface resistivity is reduced, which indicates that the present application can improve the ionic conductivity of the solid electrolyte and reduce the interface impedance by dispersing the polymer lithium salt inside the solid electrolyte and coating the surface with a conductive material.

[0097] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0098] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A solid electrolyte, characterized in that include: A base film, a polymer lithium salt and a conductive layer, wherein the polymer lithium salt is dispersed in the base film; The conductive layer is disposed on at least a portion of the surface of the base film.

2. The solid electrolyte according to claim 1, characterized in that The polymer lithium salt includes at least one of lithium carboxymethyl cellulose and lithiated polyacrylic acid.

3. The solid electrolyte according to claim 2, characterized in that The number average molecular weight of the lithium carboxymethyl cellulose is 10 5 ~10 6 ; and / or The number average molecular weight of the lithiated polyacrylic acid is 500-5000.

4. The solid electrolyte according to claim 1, characterized in that The thickness of the conductive layer is 50 nm to 2 μm.

5. The solid electrolyte according to claim 4, characterized in that The conductive layer includes at least one of a granular conductive material and a linear conductive material, preferably includes a granular conductive material and a linear conductive material; and satisfies at least one of the following conditions: The granular conductive material includes conductive carbon black; The linear conductive material includes at least one of carbon nanotubes and carbon nanofibers.

6. The solid electrolyte according to claim 5, characterized in that The conductive carbon black comprises at least one of Super P, acetylene black and Ketjen black; and / or The particle size of the conductive carbon black is 20nm to 50nm, and the specific surface area is 50m 2 / g~1500m 2 / g, oil absorption value is 300mL / 100g~800mL / 100g; and / or The carbon nanotubes have a diameter of 2nm to 30nm, a length of 5μm to 50μm, and a specific surface area of ​​300m 2 / g~1000m 2 / g; and / or The carbon nanofiber has a diameter of 100 μm to 200 μm, a length of 5 μm to 10 μm, and a specific surface area of ​​200 m 2 / g~500m 2 / g.

7. The solid electrolyte according to claim 1, characterized in that The base film satisfies at least one of the following conditions: The base film includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, and a polymer solid electrolyte; The base film has a thickness of 80 μm to 100 μm.

8. The solid electrolyte according to claim 1, characterized in that The ionic conductivity of the solid electrolyte is 10 -3 S / cm~10 -1 S / cm 。 9. A method for preparing the solid electrolyte according to any one of claims 1 to 8, characterized in that: include: The polymer lithium salt and the base film are mixed and stirred in a solvent, and vacuumed and heated to obtain a solid electrolyte membrane; The conductive material is sprayed onto the solid electrolyte membrane to obtain the solid electrolyte.

10. The method according to claim 9, characterized in that The mass ratio of the polymer lithium salt to the base film is 0.5-2.5:99.5-97.5, preferably 1-2:99-98, and most preferably 1.5:98.

5.

11. The method according to claim 9, characterized in that The stirring speed is 1000 r / min to 3000 r / min, preferably 1500 r / min to 2500 r / min, and most preferably 2000 r / min.

12. The method according to claim 9, characterized in that The heating temperature is 100°C to 150°C, preferably 110°C to 130°C, and most preferably 125°C.

13. A battery, characterized in that: The invention comprises the solid electrolyte according to any one of claims 1 to 8 or the solid electrolyte prepared by the method according to any one of claims 9 to 12.

14. An electrical device, characterized in that: Comprising the battery of claim 13.